2016
DOI: 10.1155/2016/2560710
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Whole‐Body Vibration, as a Component of the Pulmonary Rehabilitation, in Patients with Chronic Obstructive Pulmonary Disease: A Narrative Review with a Suitable Approach

Abstract: Background. Appropriate management, including pulmonary rehabilitation, associated with correct diagnosis of chronic obstructive pulmonary disease (COPD) in patients can contribute to improving clinical conditions of these patients. Physical activity is recommended for COPD patients. Whole-body vibration (WBV) is a modality of physical activity. Putting together the biological effects and safe use of WBV, it may be a potentially feasible intervention to add to pulmonary rehabilitation. The purpose of this inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Some associated physiotherapy strategies such as respiratory muscle training can produce beneficial effects in COPD subjects (Beaumont et al, 2015;Neves et al, 2014). Another strategy that has gained strength and has been associated with improvement in skeletal muscle, especially the lower limbs, and functional capacity in COPD subjects is whole body vibration, making it a potential means to recover lean mass (Braz Júnior et al, 2015;Cardim, Marinho, Nascimento, Fuzari, & Dornelas de Andrade, 2016;Sá-Caputo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some associated physiotherapy strategies such as respiratory muscle training can produce beneficial effects in COPD subjects (Beaumont et al, 2015;Neves et al, 2014). Another strategy that has gained strength and has been associated with improvement in skeletal muscle, especially the lower limbs, and functional capacity in COPD subjects is whole body vibration, making it a potential means to recover lean mass (Braz Júnior et al, 2015;Cardim, Marinho, Nascimento, Fuzari, & Dornelas de Andrade, 2016;Sá-Caputo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the efficacy of WBVE, as a form of PE, without provoking exacerbation of the disease, with several benefits for these individuals. 22,23 It is suggested that WBVE, when used as a modality of PE, under appropriated conditions, in individuals with COPD, does not lead to exacerbation of the disease, bringing several clinical benefits. Therefore, WBVE may be a great intervention in the management of these individuals, but more studies are needed.…”
Section: Efectos De Los Ejercicios De Vibración De Cuerpo Entero En Pmentioning
confidence: 99%
“…Moreover, as a mode of physical activity, WBVE has been identified as a feasible intervention with little to no adverse events [ 19 , 20 ]. WBVE has progressively been applied with beneficial outcomes to various clinical populations including stroke [ 7 , 21 ], obesity [ 22 ], rheumatoid arthritis [ 23 ], diabetes [ 24 ], spinal cord injury [ 25 ], chronic kidney disease [ 26 ], fibromyalgia [ 27 , 28 ], multiple sclerosis [ 29 ], cerebral palsy [ 30 , 31 ], Duchenne muscular dystrophy [ 32 ], osteogenesis imperfecta [ 33 ], osteoarthritis [ 34 ], and chronic obstructive pulmonary disease [ 35 ]. The effects of the WBVE may be due to neuromuscular responses to the interaction of the mechanical vibrations with the body and the tonic vibration response [ 36 – 39 ].…”
Section: Introductionmentioning
confidence: 99%